Control of vibration in a plate using active acoustic black holes. (1st March 2022) - Hook, K; Cheer, J; Daley, S
Abstract: Acoustic black holes (ABHs) are structural features that can be embedded into plates to provide effective structural damping. However, the performance of an embedded ABH is limited by its size, which determines the ABH cut-on frequency. It is not always practicable to increase the size of an ABH to reduce its cut-on frequency, however, previous work has shown that active vibration control can instead be used to enhance the low frequency performance of an ABH beam termination. This paper presents an investigation into the potential performance benefits that can be achieved by implementing active control into an array of ABHs embedded in a plate, realising an array of active ABHs (AABHs). The potential performance advantage is investigated here through experimental investigations, where different configurations of passive and active control treatments are applied to both a plate with embedded ABHs and a constant thickness plate. The smart structures utilise piezoelectric patches to realise the control actuation and employ an active feedforward multichannel vibration control strategy that aims to minimise the structural response monitored by an array of accelerometers. The performance of each plate configuration is evaluated in terms of the attenuation in the structural response and the energy, or control effort required. The presented experimental results demonstrate that, compared to the constant thickness plate configuration, the AABHs provide considerable passive damping above the ABH cut-on frequency and significantly reduce the required control effort.